2018
DOI: 10.1038/s41598-018-20932-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Study of Heart Rate Variability Responses to Changes in the Solar and Geomagnetic Environment

Abstract: This long-term study examined relationships between solar and magnetic factors and the time course and lags of autonomic nervous system (ANS) responses to changes in solar and geomagnetic activity. Heart rate variability (HRV) was recorded for 72 consecutive hours each week over a five-month period in 16 participants in order to examine ANS responses during normal background environmental periods. HRV measures were correlated with solar and geomagnetic variables using multivariate linear regression analysis wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
91
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 72 publications
9
91
0
1
Order By: Relevance
“…We collected 720-hour HRV data from 19 participants and obtained geomagnetic and solar activity. Previous studies found significant, strong correlations between HRV and geomagnetic activity 8,9 In seeming agreement with this previous work, we also found significant correlations between the two type of variables before correction for the autocorrelation inherent to time-series. After correction for autocorrelation, however, we only found a significant correlation between very low-frequency power of HRV and K index and a significant anticipatory effect on heart rate with Ap index.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We collected 720-hour HRV data from 19 participants and obtained geomagnetic and solar activity. Previous studies found significant, strong correlations between HRV and geomagnetic activity 8,9 In seeming agreement with this previous work, we also found significant correlations between the two type of variables before correction for the autocorrelation inherent to time-series. After correction for autocorrelation, however, we only found a significant correlation between very low-frequency power of HRV and K index and a significant anticipatory effect on heart rate with Ap index.…”
Section: Discussionsupporting
confidence: 93%
“…As a secondary focus, we report the effects of solar activity on HRV components. Similar to geomagnetic activity, solar activity has previously been correlated to SDNN, total power, LF, HF, VLF, and the LF/HF ratio 8,9 . Again contrasting the results of previous studies, we found no significant relationships between HRV components and solar index F10.7.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations